Economic and Legal Issues in Challenges of Energy Sector: A Global and India Perspective - Kumar, Akhilesh (Fakultas Hukum Universitas Hang Tuah, 2023)
Energy occupies a dominant role in the economic development of any country in the world. Energy sources in many countries currently rely heavily on non-renewable energy supplies. Many countries depend on non-renewable energy as a source of energy generation although recently world scientists are no longer involved in looking for ways and means to produce renewable energy. This article is an attempt to examine the legal and economic issues related to the generation, transmission and distribution of energy by comparing other energy policies with India in particular. The research method is normative juridical with statutory, conceptual and comparative approaches. The results of the study show that the global energy sector is a tapestry of diverse challenges, influenced by factors such as energy sources, geopolitical considerations, and economic development levels. India, as one of the world's most populous and rapidly developing nations, faces its unique set of challenges, including the need for energy security, sustainable growth, and environmental stewardship. India ought to begin utilization of feasible energy which neither hampers its monetary development nor impact the climate, and needs to haggle between decreasing its fossil fuel by-product to reanable product. India's journey in this sector is emblematic of the broader global trends, with its unique characteristics adding depth to the narrative. As the world strives for a sustainable energy future, collaborative efforts, innovation, and adaptive legal frameworks will be essential to addressing the myriad challenges that lie ahead.